Direct targeted therapy for MLL‐fusion‐driven high‐risk acute leukaemias. Issue 6 (22nd June 2022) - Cantilena, Sandra; Gasparoli, Luca; Pal, Deepali; Heidenreich, Olaf; Klusmann, Jan‐Henning; Martens, Joost H. A.; Faille, Alexandre; Warren, Alan J.; Karsa, Mawar; Pandher, Ruby; Somers, Klaartje; Williams, Owen; et al.
Abstract: Background: Improving the poor prognosis of infant leukaemias remains an unmet clinical need. This disease is a prototypical fusion oncoprotein‐driven paediatric cancer, with MLL ( KMT2A )‐fusions present in most cases. Direct targeting of these driving oncoproteins represents a unique therapeutic opportunity. This rationale led us to initiate a drug screening with the aim of discovering drugs that can block MLL‐fusion oncoproteins. Methods: A screen for inhibition of MLL‐fusion proteins was developed that overcomes the traditional limitations of targeting transcription factors. This luciferase reporter‐based screen, together with a secondary western blot screen, was used to prioritize compounds. We characterized the lead compound, disulfiram (DSF), based on its efficient ablation of MLL‐fusion proteins. The consequences of drug‐induced MLL‐fusion inhibition were confirmed by cell proliferation, colony formation, apoptosis assays, RT‐qPCR, in vivo assays, RNA‐seq and ChIP‐qPCR and ChIP‐seq analysis. All statistical tests were two‐sided. Results: Drug‐induced inhibition of MLL‐fusion proteins by DSF resulted in a specific block of colony formation in MLL ‐rearranged cells in vitro, induced differentiation and impeded leukaemia progression in vivo. Mechanistically, DSF abrogates MLL‐fusion protein binding to DNA, resulting in epigenetic changes and down‐regulation of leukaemic programmes setup by the MLL‐fusion protein. Conclusion: DSF can directly inhibit MLL‐fusion proteins and demonstrate antitumour activity both in vitro and in vivo, providing, to our knowledge, the first evidence for a therapy that directly targets the initiating oncogenic MLL‐fusion protein. Abstract : Direct inhibition of MLL‐fusion proteins is a potential therapeutic strategy. MLL‐fusion depletion screen identified disulfiram for its ability to ablate MLL‐fusion protein and block‐associated leukaemic phenotype. Disulfiram directly targets the CXXC domain that is essential for all MLL‐fusion proteins. Disulfiram prevents the binding to the target genes of the MLL‐fusion resulting in rapid decrease in H3K27ac levels.